Analysis of the Bearing Capacity of Piling Foundation for Bridge Structures in Clay Soils: Case Study: Cibitung - Cilincing Toll Road Project Section 3 - Resi, Aseanto; Faris, Al Rasyid (Journal of World Conference (JWC), 2020)
The Cibitung - Cilincing toll road is faced with problems across many rivers and marshlands where the swampland is identified as clay. In building construction, the foundation is very important in bearing the burden of working on the upper construction. This Final Project contains the calculation of the carrying skin capacity and the end resistance of the pile using the Suyono method. S and Nakazawa (1990) based on N-SPT data and dynamic methods using the formula of Hiley (1930) based on the pile driving record data, then proceed to the calculation of the carrying capacity of the pile group, after that calculating the decrease of the pile using the Vesic method (1977). From the results of the analysis conducted by the author in calculating the bearing capacity to using N-SPT data and pile driving record data, the author gets that from the pile diameter of 50 cm, the carrying capacity of a single-pole is 66-ton, obtained using the method of Suyono S and Nakazawa, based on the formula of Hiley, it is obtained 139.34 tons, and settlement that occurred in the pile group foundation was an immediate settlement is 11.2 cm and a consolidation settlement is 6.2 cm.